Tailoring Oxygen Reduction Reaction Kinetics of Fe-N-C Catalyst via Spin Manipulation for Efficient Zinc-Air Batteries - Zhang, Huiwen (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 Wiley‐VCH GmbH.